การศึกษาภาระ และความต้านทานของโครงสร้าง จากการบูรณะอาคารอนุรักษ์ กรณีศึกษา: ตึกโดม มหาวิทยาลัยธรรมศาสตร์ ท่าพระจันทร์ - ปะลิเตสังข์ อรณิชา; แก้วอยู่ มนัญชยา; ทองสืบสาย ภูมินทร์; รุ่งอนันต์ชัย วรวลัญช์; พุทธวรรณะ สหรัฐ (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
This article objectives are to study methods for renovating, improving, repairing, and strengthening foundation and building structure conserved by a case study of Dome Building,Thammasat University Tha Phrachan Campus. This is the first building of the university. Due to the use of the dome building for more than 87 years, the structure was damaged and deteriorated. This restoration of the dome building is the first repair since the building was built and changed the new usable area while maintaining the original identity of the dome building as much as possible to be a learning center to continue. The building had its original foundation, that was a timber foundation. and is a reinforced concrete type building It will be renovated, repaired, strengthened the original foundation, and improved the superstructure of the dome building. Then analyzed the structure loads and resistances of superstructure and substructure both before and after the renovation.